Combined Toxicity Evaluation of Ochratoxin A and Aflatoxin B1 on Kidney and Liver Injury, Immune Inflammation, and Gut Microbiota Alteration Through Pair-Feeding Pullet Model - Qing, Hanrui; Huang, Shimeng; Zhan, Kai; Zhao, Lihong; Zhang, Jianyun; Ji, Cheng; Ma, Qiugang (Frontiers in Immunology, 2022)
Ochratoxin A (OTA) and aflatoxin B1 (AFB1) are often co-contaminated, but their synergistic toxicity in poultry is limited described. Furthermore, the traditional ad libitum feeding model may fail to distinguish the specific impact of mycotoxins on the biomarkers and the indirect effect of mildew on the palatability of feed. A pair-feeding model was introduced to investigate the specific effect and the indirect effect of the combined toxicity of OTA and AFB1, which were independent and dependent on feed intake. A total of 180 1-day-old pullets were randomly divided into 3 groups with 6 replicates as each replicate contained 10 chicks. The control group (Group A) and the pair-feeding group (Group B) received the basal diet without mycotoxins contaminated. Group C was administrated with OTA and AFB1 contaminated feed (101.41 μg/kg OTA + 20.10 μg/kg AFB1). The scale of feeding in Group B matched with the feed intake of Group C. The trial lasted 42 d. Compared with the control group, co-contamination of OTA and AFB1 in feed could adversely affect the growth performance (ADFI, BW, ADG, FCR, SL); decrease the relative weight of the spleen (p < 0.01); increase the relative weight of the kidney (p < 0.01). Besides, the reduction of feed intake could also adversely affect the growth performance (BW, ADG, and SL), but not as severe as mycotoxins do. Apart from that, OTA and AFB1 also activated the anti-oxidative and inflammation reactions of chicks, increasing the level of CAT, ROS, and IL-8 while decreasing the level of IL-10 (p < 0.01), which was weakly influenced by the feed intake reduction. In addition, OTA and AFB1 induced histopathological changes and apoptosis in the kidney and liver as well as stimulated the growth of pernicious bacteria to cause toxic effects. There were no histopathological changes and apoptosis in the kidney and liver of the pair-feeding group. The combined toxicity of OTA and AFB1 had more severe effects on pullets than merely reducing feed supply. However, the proper reduction of the feed intake could improve pullets’ physical health by enriching the bacterium of the Lactobacillus, Phascolarctobacterium, Bacteroides, Parabacteroids, and Barnesiella.